An investigation into the effect of scour on the natural frequency of an offshore wind turbine. (1st June 2015) - Prendergast, L.J.; Gavin, K.; Doherty, P.
Abstract: Rapid expansion of the offshore wind industry has stimulated a renewed interest in the behaviour of offshore piles. There is widespread acceptance in practice that pile design methods developed for the offshore oil and gas industry may not be appropriate for designing wind turbine foundations. To date, the majority of offshore wind turbines are supported by large diameter monopiles. These foundations are sensitive to scour which can reduce their ultimate capacity and alter their dynamic response. In this paper, the use of a vibration-based method to monitor scour is investigated. The effect of scour on the natural frequency of a model monopile was measured in a scale model test. A spring–beam finite element numerical model was developed to examine the foundation response. The model, which used springs tuned to the small-strain stiffness of the sand, was shown to be capable of capturing the change in frequency observed in the scale test. This numerical procedure was extended to investigate the response of a full-scale wind turbine over a range of soil densities, which might be experienced at offshore development sites. Results suggest that wind turbines founded in loose sand would exhibit the largest relative reductions in natural frequency resulting from scour. Highlights: A model-scale study of scour effect on the frequency of a monopile is performed. A numerical model is developed that models the experimental response. An offshore wind turbine is modelled to investigate scour effect on frequency. A range of soil densities are investigated to assess sensitivity of initial stiffness. Wind turbines founded in loose sand exhibit the largest relative frequency reduction.